(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1977)
The AA. studied the length of the various enteric tracts as well as their full length in 40 adult bovines of European origin (20 males and 20 females) and achieved the following average, once there was no significant difference concerning sex: thin intestine ....................... 39,51m ± 3,09 caecun .................................. 0,58m ± 0,06 colon and rectun ..................... 7,08m ± 0,57 gross intestine ........................ 7,66m ± 0,59 full length ............................. 43,57m ± 2,89 On the other hand, there was no correlation between the full length of the intestine and the weight or length of the carcasses, nevertheless significant differences between the average obtained in Bos taurus and Bos indicus concerning the length of the thin intestine and the full length have been verified.